Profiling Living Conditions of the DRC Urban Population : Access to Housing and Services in Kinshasa Province - Batana, Yele Maweki; Jarotschkin, Alexandra; Konou, Akakpo; Masaki, Takaaki; Nakamura, Shohei; Viboudoulou Vilpoux, Mervy Ever (World Bank, Washington, DC, 2021)
This paper examines living conditions—mainly access to infrastructure and basic services—in Kinshasa, by focusing on how they vary within the city and how they are related to household characteristics. First, drawing on a household survey conducted in the capital province in 2018, the paper shows that many Kinshasa residents live with substandard housing and inadequate levels of access to infrastructure and basic services. Second, the level and quality of access to basic services are highly correlated with residents’ consumption and education levels, as well as their neighborhood characteristics. Third, despite the presence of negative externalities from the high population density, poor households benefit from living in dense neighborhoods by gaining a minimum level of access. The paper argues that it is imperative to increase the supply of affordable housing to lessen the inequality of access to services in Kinshasa.